Criteria for energy pricing policy : a collection of papers - Siddato, Corazon Morales, ed. (Graham and Trotman LondonGB, 1985)
Papers identify a framework for energy pricing in developing countries, considering first of all the role of pricing policy within the context of energy planning for national development. Other aspects discussed include the effect of energy pricing on economic growth, equity, industrialization, inflation and employment. Considers problems of setting producer and consumer prices of particular fuels; problems related to short-run versus long-run marginal cost pricing and also addresses practical questions regarding estimating depletion costs, inflation and relative price changes.